Mapping potential community resources and care pathways for earlier identification and recovery-oriented intervention for people with psychosis in Addis Ababa, Ethiopia - Mekonnen Tsehay; Teshome Shibre Kelkile; Wubalem Fekadu; Alex Cohen; Eleni Misganaw; Charlotte Hanlon (PLoS ONE, 2026)
Background There is a pressing need to reduce the long duration of untreated illness and improve care and outcomes for people with psychosis in Ethiopia. This study aimed to map community resources that have the potential to be leveraged to achieve earlier and more recovery-oriented interventions for people with psychosis in Addis Ababa, Ethiopia. Method A strength-based resource mapping exercise was undertaken in two sub-cities, covering an estimated population of half a million people. We identified the types of resources to be mapped, based on their importance for multi-sectoral care in mental health: healthcare facilities, religious organisations, traditional and faith healers, non-governmental organisations (NGOs), and social/community organisations. The lead investigator traversed the study sites to gather information on community resources, recorded the Global Positioning System (GPS) coordinates of the resources, and consulted with key informants. The information obtained was complemented by a participatory Theory of Change workshop attended by 30 stakeholders. Results We identified 124 health facilities, of which only 16 health centres and nine hospitals currently provide mental health services. We identified three registered traditional healers, 38 religious organisations, 104 non-governmental organisations, and other charitable/community-based organisations. In addition, three health facilities, six holy water religious healing sites, and four traditional healers were identified as out-of-site resources that were popular and frequently visited by people living in the sub-cities. The two sub-cities also had six feeding centres each providing meals for 1000 people in need. There were extensive networks of social organisations and community-based associations. Existing care pathways are complex but commonly include traditional and religious healing sites as places of first contact. Conclusions We identified important available resources that provide a wealth of opportunities for improving the early identification and outcomes of people with psychosis.